Weighted Simultaneous Approximation of the Linear Combinations of Baskakov Operators. (19th March 2020) - Tang, Xiao-jun; Wang, Xin-chang; Yi, Hua
Abstract : In this paper, the approximation property of the linear combinations of Baskakov operators is investigated by using a Jacobi weight function. Moreover, both the positive and inverse theorems for the weighted simultaneous approximation of the linear combinations of Baskakov operators are proved.